Cathelicidin Gene Expression in Porcine Tissues: Roles in Ontogeny and Tissue Specificity - Wu, Hua (American Society for Microbiology, 1999)
Cathelicidins constitute a family of mammalian antimicrobial peptides that are synthesized in the bone marrow as prepropeptides, stored in neutrophil granules as propeptides, and released as active, mature peptides upon neutrophil degranulation. We investigated the developmental expression of two porcine cathelicidins, PR-39 and protegrin. Both cathelicidins were expressed constitutively in the bone marrow of all pigs at all of the ages tested. Peripheral blood neutrophils from young pigs expressed PR-39 and protegrin mRNA, which were not detectable at 42 days of age. At earlier ages, expression of PR-39 mRNA was detected in the kidney and liver and several lymphoid organs, including the thymus, spleen, and mesenteric lymph nodes, but disappeared at 4 weeks of age. These data provide the first evidence of cathelicidin gene expression in peripheral leukocytes and may indicate a role for these antimicrobial peptides in the development of host defense mechanisms.